The word of Mahatma Gandhi and his Contribution to the Construction of a New Peru - Flores Lizana, J. Carlos (2020)
This article is an exercise in thinking about our future as a country within the oppressive framework of the global Covid 19 pandemic and on the threshold of the celebration of the bicentennial of independence, as a door to a different future. For this purpose I want to take into account the profound and positive message of the word of Gandhi, a wise man rich in humanity who, in lapidary phrases, points out the real paths of true social transformation, especially for a country with such political and social instability as the our. Methodologically, it is an essay of analysis and interpretation of selected phrases from Mahatma Gandhi’s well-known texts, orienting them to the reality of our nation.